Comorbidities in patients with psoriatic arthritis: a comparison with rheumatoid arthritis and psoriasis - Nas, Kemal; Karkucak, Murat; Durmus, Bekir; Karatay, Saliha; Capkin, Erhan; Kaya, Arzu; Ozgocmen, Salih (Wiley-Blackwell, 2015)
AimPsoriatic arthritis (PsA) is a chronic, inflammatory disease. The purpose of this study was to examine the association between PsA and comorbid conditions. This is the first study to investigate comorbid diseases in PsA in Turkey. MethodsThis study was performed under the auspices of the Anatolian Group for the Assessment in Rheumatic Diseases (ANGARD) and involved participation by six university research hospitals. Patients diagnosed with and treated for PsA on the basis of clinical, radiological and laboratory findings and expert opinion were monitored using standardized examination methods and jointly prepared forms. Clinical status, accompanying systemic diseases and surgical history were recorded. ResultsOne hundred and seventy-three patients with PsA (75 male, 98 female, mean age 41.8) and 138 patients with rheumatoid arthritis (RA) (17 male, 121 female, mean age 48.6) and 67 with psoriasis (PsO) (43 male, 24 female, mean age 36.1) were included in the study. No accompanying disease was determined in 72.8% of PsA, 50.0% of RA and 80.6% of PsO groups. In regression analysis, patients with PsA had higher risk for cataract/glaucoma surgery (odds ratio [OR]=11.99; 95% CI 1.36-105.4, P=0.025) compared to patients with RA, and higher risk for hypertension (HT) (OR=4.26; 95% CI 1.27-14.23, P=0.018) compared to the patients with PsO. ConclusionPatients with PsA have relatively lower frequency of comorbidities like diabetes mellitus, HT and cataract/glaucoma surgery compared to the patients with RA. The increased risk for having cataract/glaucoma surgery in RA compared to PsA may be particularly attributed to the more prevalent glucocorticoid use in RA.
Keywords: comorbid diseases; psoriasis; psoriatic arthritis; rheumatoid arthritis